ROAD TRANSPORT CRASHES AND SOCIO-ECONOMIC INDICATORS: A CASE OF NIGERIA - Adeyemi OMIDIJI (Journal of Construction Project Management and Innovation)
The aim of this study is to provide basis for the understanding of transport crashes as affected by socio-economic indicators with a view to providing basis for road safety policies for transport management and control in Nigeria. The objectives were to (i) examine the trend of road transport crashes in Nigeria from 1960 to 2010, (ii) identify the socio-economic development indicators and incidences that are related to road transport crashes in Nigeria, (iii) examine the road transport safety measures aimed at reducing road transport crashes and (iv) assess the contributions and challenges of road safety related agencies in the reduction of road transport crashes. Except for annual life expectancy, other socio-economic development indicators had relationship with road transport crashes in Nigeria (R2 = 0,956, p = 0.000, P<0.05). The model of this study was defined as follows: RTC= 8047.7 + 0.041(GDP) - 0.000000812 (FDI) + 0.0006 (population) - 0.0005 (vehicle) + 0.199 (telecom) – 0.388 (road length) + 0.016 (wages) – 0.001 (goods by road).  The road transport safety counter measures have reduced transport crashes by these percentages: use of seat belt (35 percent), standard speed limit signs (18 percent), speed limiters/governors (14.4 percent), use of child restraints (12.9 percent), issuance of standard licence (12 percent) and reflective pavement marking (7.7 percent). Insufficient funding (34 percent), political challenges/interferences (26 percent), lack of modern equipment and logistics (16 percent), poor training and retraining of road safety personnel (10 percent), and security challenges (8 percent) constituted the challenges of road transport crash related agencies in the reduction of road transport crashes. The study concluded that national socio-economic development indicators (Gross Domestic Product, Foreign Direct Investment, Population, Vehicle, Telecommunication, Wages, Road Length and Tonnage of Goods) have a significant relationship with road transport crashes except the annual life expectancy.